PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 013 LUBUK KEMBANG SARI KECAMATAN UKUI - Arleni Tarigan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study aims to improve student learning outcomes in social studies on the subject matterof buying and selling activities of home and school environment, with the application oflearning to play a role (role playing) in the third grade students of SD Negeri 013 LubukKembang Sari Kecamatan Ukui. Low grade III student learning outcomes SD Negeri 013Lubuk Kembang Sari Kecamatan Ukui in teaching social studies teacher is caused by notapplying the appropriate learning model in presenting the material. so that students aredifficult to understand the material presented teacher. The subjects were students of class IIIwith a whole number of students is 18 people consisting of 12 men and 6 women. Parametersmeasured were the activities of teachers, student activities and student learning outcomes.The data were analyzed descriptively. Results of data analysis obtained by percentage ofactivity the teachers at the first meeting of the first cycle of 75% with good category, thesecond meeting of the first cycle of 77.8% with good category and at the first meeting of thesecond cycle percentage teacher activity 86.1% with a very good category, the secondmeeting of the cycle II percentage teacher activity which was 88.9% with very good category.At the first meeting of the percentage of student activity activity 61.1% with good category,the second meeting of the first cycle is 77.8% with a good category and at the first meeting ofthe second cycle the percentage of student activity 80.6% with very good categories, namelythe second meeting of the second cycle 86.1% with very good category. And the classicalcompleteness students on basic score is 39.5% (not finished), the first daily test classicalcompleteness of students was 81.6% (complete), and in the daily test II classical completenessof students is 92.1% (complete). Based on this study concluded that the application oflearning models play a role (Role Playing) can improve student learning outcomes IPS.